Upaya Peningkatan Hasil Belajar Siswa Kelas V Pada Tema 8 Sub Tema 1 Melalui Model Pembelajaran Project Based Learning Di Sekolah Dasar - Budiawan Budiawan (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2020)
The Aim of this research is to increase the student's study results on theme 8 sub theme 1 in the fifth grade students of SD Negeri Ragatunjung 04, Paguyangan. Brebes in the academic year 2018/2019. This research uses Project Based Learning model and it is an Action Classroom Research. The subject of the study is the students of SD Negeri Ragatunjung 4 for 26 students in the academic year 2018/2019.  The Result of the reasearch is find out the precentages of the completeness that students achieves in the first cycle is 11 students (42,30%) success and 15 (57,70%) still get failed, which the average score 68,5. In the second cycle students succes increase in 24 students (92,30%) and 2 students (7,7%) still failed because they didn't get average score 84 yet. According to the explanation above can be concluded that using Project Based Learning Model is increasing the students study results on theme 8 sub theme 1 on the fifth grade students of SD Negeri Ragatunjung 4, Paguyangan. Brebes in the academic year 2018/2019.